Validação do questionário QLQ-CIPN20 para o português do Brasil e avaliação das suas propriedades de medida em pacientes com câncer de mama e ginecológico em tratamento com quimioterapia neurotóxica - Caires, Milena Trudes de Oliveira (2022)
Introduction: The QLQ-CIPN20 questionnaire is an instrument developed for patients with CIPN used internationally, but not validated in Brazil. Objective: To investigate the measurement properties of the QLQ-CIPN20 for Brazilian Portuguese. Material and methods: Women were recruited from an Oncology Reference Center. The QLQ-CIPN20 was applied in two moments (with an interval of 6 to 21 days), randomized, in person and by telephone. The McGill pain, neuropathic pain 4 (DN4) and quality of life questionnaires, the Quality of Life C30 (QLQ-C30) and the timed up go test (TUG) were also applied. Internal consistency was tested by Cronbach's alpha, reliability by intraclass correlation coefficient (ICC), discriminant validity by Mann Whitney and convergent validity by Spearman correlation. The Common Terminology Criteria for Adverse Events (CTCAE) was used to differentiate patients with and without CIPN. Results: One hundred and ninety women undergoing treatment for breast or gynecological cancer participated in the study, 49.4% with CIPN according to the CTCAE. Internal consistency was 0.87 and reliability was 0.76 (95% CI 0.70 – 0.82, p<0.01). The QLQ-CIPN20 questionnaire was able to discriminate patients with and without CIPN [20.5 (11 - 37) versus 6 (2 - 11) respectively (p<0.01)]. The correlation between the QLQ-CIPN20 was positive in relation to the DN4, the McGill and the symptoms scale of the QLQ-C30 and negative in relation to the functionality and overall health of the QLQ-C30 (p<0.05). There was a correlation between the TUG and the lower limbs subscale and the total QLQ-CIPN20 score in CIPN patients (r=0.36 and 0.29, respectively; p<0.05 for both). The ceiling effect was null and the floor effect was present in the autonomic subscale of CIPN patients. Conclusion: The QLQ-CIPN20 questionnaire showed adequate psychometric properties and can be applied in clinical practice.